Reforma al título i, de la infracción penal en general, del libro primero del código orgánico integral penal coip, a fin de que se incorpore la institución jurídica del delito continuado, y garantice la efectiva aplicación del principio constitucional Non Bis In Idem - Alva Jimenez, Jose Elias (2017)
Taking into account the reception which now has block of constitutionality as average guarantees for the effective enforcement of rights, we will notice that there is a need to have regulations that guarantee the correct application of constitutional principles. Under this purpose has been prepared this investigative work, specifically to achieve that our criminal law has clear and precise guidelines on the implementation of the crime continued as a legal figure that ensures the fulfillment of the principle Non Bis In Idem, determined in our Constitution (article 76, paragraph 7, literally i); that is, no person may be tried more than once for the same cause and matter. In this way, would be solved the legal problem which, in practice, has meant that people be tried several times for the same facts or causes, or of a similar nature; behaviors in accordance with doctrine and jurisprudence law of comparative law, can be judged as a same violation, because it is a continuing crime. It should be noted also, that any rule of law can restrict the content of the rights and guarantees established in the Constitution, so it does the article 11 paragraph 4 of the same; for this reason the State, he is aware that his highest duty is to respect and enforce the rights established in the Constitution, so it points out the article 11 paragraph 9 ibid.. With concerned constitutional norms, we can reveal that there is sufficient basis for our criminal legislation open the legal possibility to new precise guidelines that allow the applicability of continued crime figure.